Trypanosoma cruzi but not Trypanosoma brucei fails to induce a chemiluminescent signal in a macrophage hybridoma cell line. - Vray, B (1991)
Macrophage-Trypanosoma cruzi interactions were studied by using a newly generated macrophage hybridoma cell line (2C11-12) that was selected for its capacity to produce high levels of reactive oxygen intermediates. This cell line was found to be a suitable host cell for T. cruzi, and intracellular parasitic development could be inhibited by activation with gamma interferon. When exposed to opsonized Trypanosoma brucei, Micrococcus lysodeikticus, or Legionella pneumophila, the activated macrophage cell line produces a high chemiluminescent signal, indicating the release of reactive oxygen intermediates. Alternatively, when opsonized T. cruzi was added to these activated macrophages, this parasite failed to stimulate a chemiluminescent response, suggesting an impairment in the triggering of the respiratory burst.